Realizacja funkcji fiskalnej podatków pośrednich - Sosnowski, Michał (The Implementation of Fiscal Function of Indirect Taxes, 2009)
In this article, the author focuses on indirect taxes in terms of the implementation of fiscal function. For this purpose there were discussed the importance of fiscal functions, features, advantages and disadvantages of indirect taxes. Moreover, there were put forward the realized tax revenue to the central budget for the period 2003-2007. In conclusion, it was found that the optimal proportion between direct and indirect taxes to impose the tax burden can further promote the stable development of economy of the country
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 306-315